Dorsal penile nerve block alleviates pain in men undergoing rigid cystoscopy: A single‐center, randomized, double‐blind, and placebo‐controlled trial. Issue 4 (5th February 2021) - Qiu, Yan; Liu, Xinhao; Wei, Wuran; Du, Guizhi
Abstract: Objective: To assess the effectiveness and safety of dorsal penile nerve block (DPNB) compared with tetracaine gel in analgesia for men undergoing rigid cystoscopy. Patients and methods: This study was conducted as a prospective, randomized, double‐blind, placebo‐controlled, and single‐center trial. Men undergoing diagnostic rigid cystoscopy were randomly allocated into one of three groups (n = 86 each): (1) tetracaine gel group (DPNB with saline), (2) DPNB group (DPNB with ropivacaine + plain lubricant), and (3) combination group (DPNB with ropivacaine + tetracaine gel). The primary outcome was visual analog scale (VAS) for pain at cystoscopic inspection of the external sphincter. Results: VAS (median [interquartile]) at inspection of the external sphincter was significantly lower in both DPNB and combination groups than that in tetracaine gel group (4 [3–6] and 4 [3–5] vs 6 [5–7], P < .0001), with a 33% reduction of median VAS. Overall pain level during procedure was significantly alleviated in the DPNB and combination groups with more stabilized HR and MAP when compared with tetracaine gel group. No adverse events were observed during DPNB including penile hematoma, erection, local anesthetic toxicosis or incompletion of cystoscopy. Conclusion: Our study suggests analgesia provided by DPNB with or without tetracaine gel instilled is superior to that provided by tetracaine gel alone in men undergoing diagnostic rigid cystoscopy. Clinical Trials Registration: ClinicalTrials.gov registration number: NCT02502487.